Jade the disco fairy - Meadows, Daisy (New York : Scholastic, Inc., 2007)
Dances are getting off on the wrong foot because the dance fairies' magic ribbons are missing and the disco at Kirsty's school won't be the same without Jade's magic ribbon.
RL2.
006-009.
Keywords: Walker, Rachel (Fictitious character) -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Walker, Rachel (Fictitious character) -- Fiction; Tate, Kirsty (Fictitious character) -- Fiction; Fairies -- Fiction